(untitled) (European journal of volunteering and community-based projects, 2025)
The study explores the relationship between AI adoption and ESG performance, addressing a gap in literature. AI enhances sustainability by improving environmental monitoring, optimizing resource allocation, and fostering circular economy initiatives. Socially, AI promotes diversity and workplace well-being through advanced algorithms, while in governance, it strengthens oversight, risk assessment, and compliance. Using Bloomberg data on U.S. and Western European companies, the study tests whether ethical AI policies impact ESG scores. The results confirm a significant positive effect, suggesting that responsible AI adoption strengthens corporate transparency, investor trust, and decision-making.